A Critical Edition Of Al-Tabari’s Badi‘iyyah Entitled Ashraf Al-Bishr Bi-Madḥ Ashraf Al-Bashar/تحقيق بديعية الطبري المسماة أشرف البِشَر بمدح أشرف البَشر - Mahmud Şuş; Aslam Jankir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study presents a critical edition of the Badīʿiyya manuscript entitled Eşrefü’l-Beşer’i Medheden Eşrefü’l-Beşer, composed in the 11th century AH in Mecca by ʿAbd al-Qādir b. Muḥammad al-Ṭabarī al-Makkī (d. 1033 AH/1623 AD). The research aims to investigate al-Ṭabarī’s contributions to Arabic rhetorical terminology, analyze the poetic application of Badīʿ devices within the text, and present the manuscript in a reliable scholarly form. Adopting a descriptive and comparative methodology, the study relies on classical rhetorical sources for textual emendation and verification (ḍabṭ). A significant finding of this research lies in the manuscript's prose introduction, which provides concise definitions for over one hundred rhetorical terms, reflecting the scholarly conventions of the late rhetorical school. The study reveals that al-Ṭabarī systematically integrated these devices into a unified poem following the basīṭ meter and a single rhyme, successfully bridging theoretical exposition with practical poetic illustration. The edition, based on the sole extant manuscript, addresses scribal errors through contextual evidence and established literature. The study concludes that this Badīʿiyya serves as a vital primary source for tracing the evolution of late Arabic rhetorical traditions and the development of the Badīʿiyyāt genre.